Synthesis and Characterization of A New Ligand (DPTYEDAPIBO) Derived from 2-Aminothiazole and Preliminary MCF-7 Cytotoxicity Evaluation - Abbas Fadhil Yasir; Hayder Obaid Jamel (College of Pharmacy University of Baghdad, 2024)
A series of new complexes were prepared by ligand (DPTYEDAPIBO) interaction with the following metal chlorides: Ni (II), Cu (II), and Pt (IV), as well as AgNO3 dissolved in ethanol. The ligand (DPTYEDAPIBO) is prepared in three steps: The first step is the preparation of compound (A) which is prepared from the reaction of 2-Aminothiazol in ethanol solvent with Benzil. The second step involves the reaction of benzene-1,2-diamine with (E)-3-(hydroxyamino) butan-2-one to form compound (B). As for the third step, it involves the reaction of the product of the first step, compound (A), with the product of the second step, compound (B), to form the ligand. The structures of the ligand and its complexes are confirmed by FT-IR, 1H-13C-NMR, and UV-Vis spectra, melting points, molar conductivity, elemental analyses (CHN), and magnetic susceptibility measurements. The synthesized complexes are prepared in a (1:1) ratio (M:L) for each of the Ni (II), Cu (II), Ag (I), and Pt (IV) complexes. These measurements suggest octahedral geometry for each of the Ni (II), Cu (II), and Pt (IV) complexes and tetrahedral geometry for the Ag (I) complexes. Each of the ligands and the platinum complex were tested for anticancer activity, and it was discovered that the platinum complex is more effective against breast cancer cells (MCF-7) while having less effect on normal cells (WRL-68). An antioxidant test was also performed for the prepared compounds.